2021
DOI: 10.1111/1749-4877.12590
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota and host metabolic divergence are associated with the adaptation of Diploderma vela to spatially heterogeneous environments

Abstract: Heterogeneous environment adaptation is critical to understand the species evolution and response to climate change. However, how narrow-range species adapt to micro-geographic heterogeneity has been overlooked, and there is a lack of insights from metabolism and commensal microbiota. Here, we studied the environmental adaptation for 3 geographic populations (>40 km apart) of Diploderma vela, a lizard endemic to dry-hot valleys of the Hengduan Mountain Region. The climatic boundary caused a cooler, droughtier,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…1 This information is detailed in Supplementary Table 1 . The gut microbiome and tissue metabolomics data of D. vela have been published previously ( Zhu et al, 2021c ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 This information is detailed in Supplementary Table 1 . The gut microbiome and tissue metabolomics data of D. vela have been published previously ( Zhu et al, 2021c ).…”
Section: Methodsmentioning
confidence: 99%
“…Extracted supernatants were analyzed by LC (1,290 Infinity LC, Agilent) coupled with quadrupole-time-of-flight mass spectrometry (Triple TOF 5,600 +, AB SCIEX). The details in the metabolic profiling followed the methods described by Zhu et al (2021c) . Metabolite data were processed using XCMS software 2 and Microsoft Excel (Microsoft, Redmond, WA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this spirit, Integrative Zoology publishes one more special subsection in this issue. Zhu et al (2022) revealed that the adaptation of animal gut microbiota and metabolic characters to spatial heterogeneous environments could provide mechanistic insights into the evolution and enable reliable prediction on population distribution with climate change. This multi-omics study found that Diploderma vela populations with different climatic background showed significant divergence in their muscle and liver metabolome and gut commensal microbiota, and this was not observed between populations that shared similar climatic factors despite of comparable geographical distance.…”
Section: Intestinal Microbiota In Various Animalsmentioning
confidence: 99%